Timing anthropogenic stressors to mitigate their impact on marine ecosystem resilience. Issue 1 (December 2017) - Wu, Paul; Mengersen, Kerrie; McMahon, Kathryn; Kendrick, Gary; Chartrand, Kathryn; York, Paul; Rasheed, Michael; Caley, M. Julian
Abstract Better mitigation of anthropogenic stressors on marine ecosystems is urgently needed to address increasing biodiversity losses worldwide. We explore opportunities for stressor mitigation using whole-of-systems modelling of ecological resilience, accounting for complex interactions between stressors, their timing and duration, background environmental conditions and biological processes. We then search for ecological windows, times when stressors minimally impact ecological resilience, defined here as risk, recovery and resistance. We show for 28 globally distributed seagrass meadows that stressor scheduling that exploits ecological windows for dredging campaigns can achieve up to a fourfold reduction in recovery time and 35% reduction in extinction risk. Although the timing and length of windows vary among sites to some degree, global trends indicate favourable windows in autumn and winter. Our results demonstrate that resilience is dynamic with respect to space, time and stressors, varying most strongly with: (i) the life history of the seagrass genus and (ii) the duration and timing of the impacting stress. Stressors such as sediment dredging can harm marine organisms, but this impact could be minimised if targeted within 'ecological windows'. Here, Wu and colleagues develop a modelling framework to identify ecological windows that maximise seagrass resilience under varying dredging schedules.